A (IN)CONSTITUCIONALIDADE DA EXECUÇÃO PROVISÓRIA DE PENA PROFERIDA PELO TRIBUNAL DO JÚRI: Análise à luz do princípio da presunção de inocência e da tese fixada no julgamento das ADCs 43, 44 e 54 pelo Supremo Tribunal Federal - RODRIGUES, MARIANA (2023)
This academic work analyzes the constitutionality of the provisional execution of the sentence handed down by the Jury, using as parameters the principle of presumption of innocence and the thesis established in the judgment of the Declaratory Actions of Constitutionality nº 43, 44 and 54 by the Federal Supreme Court. To do so, it studies: the repercussion of the Constitution in current Brazilian law, especially in infra-constitutional criminal procedural legislation; the principle of presumption of innocence, according to the provisions of article 5, LVII, of the Constitution; the legal discussions and the thesis established in the trial of the Declaratory Actions of Constitutionality nº 43, 44 and 54 by the Federal Supreme Court; the Jury, especially the procedural rite that results in a conviction and the article 492, item I, line 'e', of the Code of Criminal Procedure; and the trial of the Theme 1.068 of the Supreme Court. With that, the study verifies the incompatibility of the early execution of the sentence in the scope of the Jury with the current constitutional order, especially with the principle of presumption of innocence. Thus, the thesis defends the unconstitutionality of article 492, item I, line 'e', of the Code of Criminal Procedure and the establishment of the following thesis for Theme 1.068 of the STF: "Considering the guarantee of the presumption of innocence, versed in art. 5, subsection LVII, of the Federal Constitution, it is unconstitutional the early execution of sentence issued by the Jury, in order to ensure every convicted person the right to appeal; but the preventive detention may be decreed motivated, as a precautionary measure, pursuant to article 312 of the Penal Procedure Code, by the Presiding Judge from the facts and grounds established by the Jurors"